Micronucleus Test of Picrorrhiza Rhizoma Aqueous Extract in Bone Marrow Cells of Male ICR Mice - Chung, I.K., Daegu Haany University, Gyeongsan, Republic of Korea; Cheon, W.H., Daegu Haany University, Gyeongsan, Republic of Korea; Ku, S.K., Daegu Haany University, Gyeongsan, Republic of Korea (Toxicological research (Seoul), 2011)
In this research, the genotoxic effect of Picrorrhiza Rhizoma (PR) aqueous extract was evaluated using the mouse micronucleus test. PR extract was administered once a day for 2 continuous days by oral gavage to male ICR mice at doses of 2000, 1000 and 500 mg/kg. Cyclophosphamide was used as a known genotoxic agent in a positive control. The appearance of a micronucleus (MN) in polychromatic erythrocyte (PCE) is used as an index for genotoxic potential, and PCE ratio is used as an index of cytotoxicity. Although significant (p less than 0.01) increase of the number of PCE with one or more nuclei (MNPCE) was detected in cyclophosphamide treated groups, no significant increases of MNPCE numbers were observed in all three different dosages of PR extracts treated mice with over 0.39 of the individual polychromatic erythrocyte ratio in all mice used in this study. The results obtained indicated that PR extract shows no genotoxicity effects up to 2000 mg/kg dosing levels.